1978
DOI: 10.1037/h0077542
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6-hydroxydopamine lesions of the nucleus accumbens septi and olfactory tubercle on feeding, locomotor activity, and amphetamine anorexia in the rat.

Abstract: Bilateral 6-hydroxydopamine lesions of the nucleus accumbens septi (NAS) and olfactory tubercle (OT) caused enhanced intake of wet mash in 23-hrfood-deprived rats tested in photocell activity cages during restricted 30-min sessions. This mild hyperphagia was accompanied by a significant hypoactivity in the group with NAS/OT lesions. No hyperphagia was observed during a prolonged 120-min test session or in free-feeding tests conducted in the home cage. Anorexia induced by d-amphetamine (.5 and 1.5 mg/kg) was un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
142
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(153 citation statements)
references
References 24 publications
10
142
1
Order By: Relevance
“…The pattern is reminiscent of those observed in studies with rodents, in which effects of manipulating dopamine in the ventromedial striatum are more readily observed on preparatory than on consummatory behaviors (Robbins and Everitt, 1992;Salamone et al, 2007). Moreover, some studies have reported that consummatory responses can be attenuated by increases in dopamine (eg after amphetamine administration, which can have anorexic effects; eg Bakshi and Kelley, 1991; but see Kelley et al, 1989), and enhanced by decreases in dopamine (eg by 6-OHDA lesions; see Baldo and Kelley, 2007;Koob et al, 1978). Instead, it has been postulated that opioids directly modulate consummatory responses (Berridge and Robinson, 1998).…”
Section: Role Of Dopamine In Motivation and Cognitionmentioning
confidence: 64%
“…The pattern is reminiscent of those observed in studies with rodents, in which effects of manipulating dopamine in the ventromedial striatum are more readily observed on preparatory than on consummatory behaviors (Robbins and Everitt, 1992;Salamone et al, 2007). Moreover, some studies have reported that consummatory responses can be attenuated by increases in dopamine (eg after amphetamine administration, which can have anorexic effects; eg Bakshi and Kelley, 1991; but see Kelley et al, 1989), and enhanced by decreases in dopamine (eg by 6-OHDA lesions; see Baldo and Kelley, 2007;Koob et al, 1978). Instead, it has been postulated that opioids directly modulate consummatory responses (Berridge and Robinson, 1998).…”
Section: Role Of Dopamine In Motivation and Cognitionmentioning
confidence: 64%
“…Indeed, acute intracortical injection of DA into frontal regions of adult rats has been reported to attenuate responsiveness to systemically administered stimulants [272] as well as to disrupt expression of sensitization to cocaine [435], data reminiscent of the similarly reduced response of adolescent rats to acute stimulant exposure [51,308,313,491,507,510,511] and attenuated expression of cocaine sensitization [507]. Likewise, adult rats with 6-OHDA lesions of DA input to ACC, like their normal adolescent counterparts (as discussed earlier), are hyperphagic [160,296], less sensitive to locomotor activating effects of psychomotor stimulant drugs [296], and exhibit problems adjusting to alterations in reward contingencies (see Ref. [317] for review and references).…”
Section: Behavioral Correlates Theoretical Considerations and Some Cmentioning
confidence: 86%
“…Experimentally enhanced DA function increases behavioral activity, whereas lesions of the ML-DA system reduce or eliminate exploratory and appetitive-approach behaviors (Koob et al, 1978;Fink & Smith, 1980;Robbins & Everitt, 1982;Taghzouti, 1985;Pierce et al, 1990;Pfaus & Phillips, 1991;Jones & Robbins, 1992;Liu et al, 1998). Pharmacological reduction of Nacc DA transmission inhibits seekingapproach behaviors in response to reward-associated cues (Blackburn et al, 1992;Di Ciano et al, 2001;Parkinson et al, 2002;Wakabayashi et al, 2004).…”
Section: Microinjections and Lesion Studiesmentioning
confidence: 99%